Influencing Factors of Recessive Dropout of Rural Junior High School Students - Chang, Jing; g, Jing Chan; Jun, Chen (Journal of Theory and Practice of Management Science, 2023)
Through the relevant questionnaires to investigate the influencing factors of the hidden dropout of some rural junior high school students in Ningde area, to understand the reasons behind the hidden dropout of rural junior high school students, and to analyze the influence of individuals, families, schools and society on the hidden dropout of rural junior high school students. Individuals, parents, schools, society and other parties work together to solve the problem of hidden dropouts and enable rural junior high school students to study well. In the process of music education in traditional vocational colleges, the employment direction and space of relevant students are relatively lack. When music students graduate, most of them work in basic music education units, unable to play their own value role in the construction and development of the music industry.